Perilaku Keterlambatan - Setiono, Daniel; Garren, Joel; Ardiyanto, Farrel; Yudiarso, Ananta (Jurnal Ilmiah Psyche, 2024)
The purpose of this study is to explore tardiness behavior. This study focuses on studies from the perspective of psychology, sociology and anthropology. The method used in this study is a qualitative method. Three participants were involved in this study. The results of this study found that the main cause of tardiness behavior is the lack of dominance of rules or policies. From a psychological perspective, tardiness behavior can be explained using the theory of cognitive developmental psychology. This theory explains that tardiness behavior can be caused by several intrinsic elements in students. From a sociological perspective, tardiness behavior is analyzed using the affective dominance theory and the traditional rationality model. From an anthropological perspective, tardiness behavior is a type of polychronic time. This concept explains that individuals usually see time only as fluid and their main focus is on social relationships rather than efficiency to arrive on time.